Practice toward standardized performance testing of computer-aided detection algorithms for pulmonary nodule - Wang, Hao; Tang, Na; Zhang, Chao; Hao, Ye; Meng, Xiangfeng; Li, Jiage (Frontiers in Public Health, 2022)
This study aimed at implementing practice to build a standardized protocol to test the performance of computer-aided detection (CAD) algorithms for pulmonary nodules. A test dataset was established according to a standardized procedure, including data collection, curation and annotation. Six types of pulmonary nodules were manually annotated as reference standard. Three specific rules to match algorithm output with reference standard were applied and compared. These rules included: (1) ‘center hit’ (whether the center of algorithm highlighted region of interest (ROI) hit the ROI of reference standard); (2) ‘center distance’ (whether the distance between algorithm highlighted ROI center and reference standard center was below a certain threshold); (3) ‘area overlap’ (whether the overlap between algorithm highlighted ROI and reference standard was above a certain threshold). Performance metrics were calculated and the results were compared among ten algorithms under test (AUTs). The test set currently consisted of CT sequences from 593 patients. Under ‘center hit’ rule, the average recall rate, average precision, and average F1 score of ten algorithms under test were 54.68%, 38.19%, and 42.39% respectively. Correspondingly, the results under ‘center distance’ rule were 55.43%, 38.69% and 42.96%, and the results under ‘area overlap’ rule were 40.35%, 27.75% and 31.13%. Among the six types of pulmonary nodules, the AUTs showed the highest miss rate for pure ground-glass nodules, with an average of 59.32%, followed by pleural nodules and solid nodules, with an average of 49.80% and 42.21%, respectively. The algorithm testing results changed along with specific matching methods adopted in the testing process. The AUTs showed uneven performance on different types of pulmonary nodules. This centralized testing protocol supports the comparison between algorithms with similar intended use, and helps evaluate algorithm performance.